Effective delivery of input services (AI, feed and veterinary services) to livestock development in Ethiopia - Ergano, Kebebe; Duncan, Alan J. (International Livestock Research Institute, 2010)
The IFAD-Funded ‘Fodder Adoption Project’ (FAP) uses feed scarcity as an entry point to address major constraint in livestock development in selected districts in Ethiopia. It also recognizes that fodder scarcity is not just about technologies but also about the collective capacity of a network of individuals and organizations. It therefore uses an innovation system framework to engage multiple actors along livestock commodity value chains–facilitating continuous interaction among stakeholders to generate innovation rather than just research products or technologies. The Fourth Ethiopian Fodder Roundtable was held on the theme of ‘Role of effective delivery of input services (AI, veterinary services, and feed) to fodder/dairy development in Ethiopia’. The roundtable discussions were facilitated based on discussion points emerging from brief PowerPoint presentations. The presentations outlined some key constraints contributing to feed scarcity in Ethiopia: the subsistence mode of production; poorly developed market for livestock products; chronic shortage of fodder biomass; dominance of arable production; feed being an intermediate commodity; weakness of private sector; and an extension system which focuses on the cereal sector. AI provision in Ethiopia is weak due to the constraints associated with lack of breeding policy, lack of regular monitoring of bulls for reproductive performance, absence of a herd registration and recording system, poor technical, financial and managerial support and poor networking of the service. Formation of dairy farmers associations, a cattle breeders association and establishing private business associations were suggested as options for effective delivery of AI services.